2019
DOI: 10.1177/0018578719890090
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Pharmaceutical Production in Thai Hospitals

Abstract: Purpose: The purpose of this research was to provide an overview of pharmaceutical production in Thai hospitals. Methods: A cross-sectional survey was developed to study pharmaceutical production in the 1347 Thai hospitals. A representative sample was chosen using multistep selection arriving at a final total of 750 hospitals. Five experts in hospital pharmacy production were recruited to evaluate the content validity. The questionnaire consisted of 2 parts: (1) general details of the hospitals and (2) the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The study population comprised 395 hospitals in Thailand that reported having on-premise pharmaceutical production facilities. These hospitals were selected based on their prior participation in a comprehensive survey conducted by Pichayajittipong et al 19 These hospitals were included to gather robust data and valuable insights regarding extemporaneous pharmaceutical production practices within the country. This meticulous approach ensured the representation of a diverse and representative sample of hospitals engaged in pharmaceutical production, thereby enhancing the validity and generalizability of the findings.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population comprised 395 hospitals in Thailand that reported having on-premise pharmaceutical production facilities. These hospitals were selected based on their prior participation in a comprehensive survey conducted by Pichayajittipong et al 19 These hospitals were included to gather robust data and valuable insights regarding extemporaneous pharmaceutical production practices within the country. This meticulous approach ensured the representation of a diverse and representative sample of hospitals engaged in pharmaceutical production, thereby enhancing the validity and generalizability of the findings.…”
Section: Study Populationmentioning
confidence: 99%
“…18 Furthermore, Pitchayajittipong et al reported that extemporaneous preparations constitute the highest number of pharmaceutical products in Thai hospitals. 19 This study aimed to address the existing gap in comprehensive reporting by investigating the extent of variation in extemporaneous preparations in Thai hospitals. Through a meticulous examination of the current state of practice, identification of challenges, and exploration of potential areas for improvement, this study aims to provide valuable insights into the distinctive landscape of compounding in Thailand compared with other countries.…”
Section: Introductionmentioning
confidence: 99%